Intracystic papillary neoplasm of the gallbladder concomitant with xanthogranulomatous cholecystitis: a case report - Takashi Aida; Masashi Tsunematsu; Kenei Furukawa; Koichiro Haruki; Yoshihiro Shirai; Shinji Onda; Yoichi Toyama; Kazutaka Gomisawa; Hiroyuki Takahashi; Toru Ikegami (Surgical Case Reports)
Abstract Background The intracystic papillary neoplasm (ICPN) is a newly established disease concept. It has been regarded as a preinvasive neoplastic lesion, similar to intraductal papillary mucinous neoplasm of the pancreas. Limited information is available on the clinical and imaging features of ICPN. Case presentation A 65-year-old woman was referred to our hospital for assessment of a gallbladder tumor. Contrast-enhanced computed tomography showed a papillary tumor in the fundus of the gallbladder with irregular thickening of the gallbladder wall that spread into the cystic duct. The boundary between the tumor and liver was unclear. The patient was diagnosed with gallbladder cancer with liver invasion. We performed extended cholecystectomy with liver bed resection after confirming the absence of cancer cells in the resection margin of the cystic duct. After pathological examination, the tumor was diagnosed as an ICPN with xanthogranulomatous cholecystitis. The patient was discharged on postoperative day 8 with no complications. Conclusions We have described a rare case of ICPN concomitant with xanthogranulomatous cholecystitis. Clinicians should include ICPN as a differential diagnosis in patients with a papillary or polypoid tumor in the gallbladder.